2012
DOI: 10.1007/s10557-012-6411-3
|View full text |Cite
|
Sign up to set email alerts
|

The Beneficial Effects of a Direct Thrombin Inhibitor, Dabigatran Etexilate, on the Development and Stability of Atherosclerotic Lesions in Apolipoprotein E-deficient Mice

Abstract: DE attenuates arterial thrombosis, reduces lesion size and may promote plaque stability in ApoE-/- mice. The plaque-stabilizing effects of chronic thrombin inhibition might be the result of the favorable modification of inflammatory mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 33 publications
3
59
1
2
Order By: Relevance
“…Furthermore, both valvular and arterial calcification have been reported in animals on warfarin treatment 17. By contrast, limited data from experimental animal studies have indicated a potentially beneficial effect of novel, direct‐acting anticoagulants on the development and progression of atherosclerosis 18, 19, 20…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, both valvular and arterial calcification have been reported in animals on warfarin treatment 17. By contrast, limited data from experimental animal studies have indicated a potentially beneficial effect of novel, direct‐acting anticoagulants on the development and progression of atherosclerosis 18, 19, 20…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, pharmacological treatment of mice on an apoE 2/2 background with the selective thrombin inhibitor dabigatran or with 1 of the factor Xa inhibitors melagatran or rivaroxaban clearly indicates that targeting 1 coagulation protease diminishes atherogenic features of vascular endothelium and reduces plaque burden. 29,[32][33][34] Collectively, one may postulate that in the case of hemophilia, where the lack of factor VIII reduces basal levels of thrombin generation, this may (favorably) affect the plaque phenotype rather than the plaque load, which is driven by stronger factors including hypertension. Both the strength and the direction of the effect of hypocoagulability will be influenced by age, gender, genetic background, and cardiovascular risk factors.…”
Section: Atherosclerosis In Patients With Hemophiliamentioning
confidence: 99%
“…In the context of atherogenesis and atherosclerosis, TG is linked to early atherosclerosis, likely one of the drivers of this complex process 75. This model is strongly supported by experimental studies 22, 23, 24, 25…”
Section: Biochemical Mechanisms Linking Thrombin To Atherothrombosismentioning
confidence: 72%